Record‐Strong Eastward Propagating 4‐Day Wave in the Southern Hemisphere Observed During the 2019 Antarctic Sudden Stratospheric Warming - Jiahui Luo; Zheng Ma; Yun Gong; Shaodong Zhang; Qiao Xiao; Chunming Huang; Kaiming Huang (Geophysical Research Letters)
Abstract Based on the zonal winds from the Modern‐Era Retrospective Analysis for Research and Applications, version 2 reanalysis data, we investigate the enhancement of an eastward propagating 4‐day wave (E4DW) during the 2019 Antarctic sudden stratospheric warming (SSW). The amplitudes of E4DW are centered at 50°S and 50 km with a maximum amplitude of ∼20 m/s. The enhanced E4DW significantly exceeds the climatological level and has the strongest amplitude in the Southern Hemisphere since 1980. Our results show that the E4DW is generated by the atmospheric instabilities via a double‐jet configuration of the zonal mean zonal winds. Our analysis further indicates that the special structure of the zonal mean zonal winds caused by the 2019 Antarctic SSW at the stratopause is responsible for the excitation of the record‐strong E4DW in 2019 in the Southern Hemisphere.